n Sistematisering van die industriele groeiproses van Japan, 1868-1960 - Coetzee, Nicolaas Petrus (Stellenbosch : Stellenbosch University, 2012)
Proefskrif (M.Comm.) -- Universiteit van Stellenbosch, 1969.